Oil and gas exploration in Cuba : geological-structural cartography using potential fields and airborne gamma spectrometry /: geological-structural cartography using potential fields and airborne gamma spectrometry. (2017) - Echarte, Manuel Enrique Pardo; Reguera, Jorge Luis Cobiella
No abstract available